Evolution and diversification within the intertidal brown macroalgae Fucus spiralis/F. vesiculosus species complex in the North Atlantic - Coyer, J. A.; Hoarau, G.; Costa, J. F.; Hogerdijk, B.; Serrão, Ester; Billard, E.; Valero, Myriam; Pearson, G. A.; Olsen, J. L. (Elsevier, 2014)
We examined 733 individuals of Fucusspiralis from 21 locations and 1093 Fucusvesiculosus individuals from 37 locations throughout their northern hemisphere ranges using nuclear and mitochondrial markers. Three genetic entities of F. spiralis were recovered. In northern and sympatric populations, the presence of "F. spiralis Low" in the mid-intertidal and "F. spiralis High" in the high-intertidal was confirmed and both co-occurred with the sister species F. vesiculosus. The third and newly-discovered entity, "F. spiralis South", was present mainly in the southern range, where it did not co-occur with F. vesiculosus. The South entity diverged early in allopatry, then hybridized with F. vesiculosus in sympatry to produce F. spiralis Low. Ongoing parallel evolution of F. spiralis Low and F. spiralis High is most likely due to habitat preference/local selection and maintained by preferentially selfing reproductive strategies. Contemporary populations of F. spiralis throughout the North Atlantic stem from a glacial refugium around Brittany involving F. spiralis High; F. spiralis South was probably unaffected by glacial episodes. Exponential population expansion for F. vesiculosus began during the Cromer and/Holstein interglacial period (300,000-200,000 yrs BP). Following the last glacial maximum (30,000-22,000 yrs BP), a single mtDNA haplotype from a glacial refugium in SW Ireland colonized Scandinavia, the Central Atlantic islands, and the W Atlantic.